Restating Orientalism : a critique of modern knowledge - Hallaq, Wael B., 1955- (Columbia University Press, 2018)
"Edward Said's Orientalism not only inaugurated a new and highly controversial arena of discourse but also set the terms of debate around knowledge, power, and imperialism since 1978, when the book first appeared. The substance of discussions remains extensively political, limited to the so-called problem of knowledge and power and the complicity of Orientalism in the larger project of colonialism. One of the many critiques was that Said was too sweeping in his condemnation of Orientalists, leaving no analytical space for distinguishing degrees of difference between one scholar and another. Thus any scholar who depicts Islam negatively or too positively is an Orientalist, the former a bigot of some sort and the latter an exoticizer. Restating Orientalism offers an alternative account that accepts and transcends political thought and positioning while avoiding the totalization of authorial condemnation in Said's narrative. Hallaq reopens the problem of power and knowledge to an ethical critique, asking such questions as: What makes certain forms of knowledge useful to power, and what kind of cultural configurations exist in the world in which knowledge and power have virtually no relationship with each other? Refusing to isolate or scapegoat Orientalism, the book extends the critique to other academic fields, tracing their involvement in colonialism and genocide to a seventeenth- and eighteenth- century structure of thought whose most salient characteristic was a type of domination anchored in sovereignty over life and death. Orientalism, Hallaq argues, is no more an exception to liberal and modern forms of knowledge than genocide in general was an exception in modernity, but rather is the truest representation of modern sovereign capabilities"--